Adaptasi era kenormalan baru di bidang radiologi kedokteran gigi: apa yang perlu kita ketahui - Muhammad Novo Perwira Lubis; Fadhlil Ulum Abdul Rahman (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: COVID-19 has caused a negative impact and paralysis in the activities of the dentistry field because it has a high risk of contamination and transmission of the SARS-Cov-2. Even so, dental services cannot stop completely, especially for emergency cases, so that a new form of adaptation of normality is recommended for all dental services including the dentomaxillofacial radiology. This article aims to discuss the adaptation to the new normal era of in the dentomaxillofacial radiology examinations. Literature Review: The use of dentomaxillofacial radiographic examinations is indispensable for diagnosis and determination of treatment plans, but in the era of the COVID-19 pandemic and this new normal era, modifications are needed in stricter infection control in dentomaxillofacial R\radiology installations to prevent as much as possible the possibility of virus transmission SARS-Cov-2. The application of room controls, medical personnel, x-ray equipment, patients, and radiograph documents are very important in carrying out the adaptation to this new normal era. Conclusion: An adequate infection control and application of teleradiology are important things to be considered and implemented as a form of adaptation to new normal in dentomaxillofacial radiology installations in patient care as a way to prevent transmission and contamination of the SARS-Cov-2 virus during the COVID-19 pandemic.